2018
DOI: 10.5114/ceji.2018.81359
|View full text |Cite
|
Sign up to set email alerts
|

The level of myeloid-derived suppressor cells positively correlates with regulatory T cells in the blood of children with transient hypogammaglobulinaemia of infancy

Abstract: IntroductionTransient hypogammaglobulinaemia of infancy (THI) is a primary immunodeficiency characterised by low levels of immunoglobulin G (often with concomitant decrease of IgA and sometimes also of IgM) with still unknown exact reason. A delayed normalisation of the immunoglobulin level in THI may be associated with a transiently elevated number of regulatory T cells (Treg). Although in cancer and chronic inflammation it was shown that the level of Treg cells can be increased by myeloid-derived suppressor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
2
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…Both of these non-classical lymphocyte subsets have been studied and described for their role in cancer surveillance (6, 14, 15). On the other hand, in the putative cancer-enhancing/immune-suppressive cluster, we observed an association between circulating M-MDSC and Tregs that might be explained by increase in Tregs induced by MDSC-derived immunosuppressive cytokines (16) as described previously in non-cancer settings (17, 18). NLR associated with M-MDSC and Tregs, which may reflect “emergency” myelopoiesis induced by tumor or by host-related conditions, that promotes production of not only classical myeloid cells such as neutrophils and monocytes but also myeloid-derived suppressor cells (19).…”
Section: Discussionsupporting
confidence: 77%
“…Both of these non-classical lymphocyte subsets have been studied and described for their role in cancer surveillance (6, 14, 15). On the other hand, in the putative cancer-enhancing/immune-suppressive cluster, we observed an association between circulating M-MDSC and Tregs that might be explained by increase in Tregs induced by MDSC-derived immunosuppressive cytokines (16) as described previously in non-cancer settings (17, 18). NLR associated with M-MDSC and Tregs, which may reflect “emergency” myelopoiesis induced by tumor or by host-related conditions, that promotes production of not only classical myeloid cells such as neutrophils and monocytes but also myeloid-derived suppressor cells (19).…”
Section: Discussionsupporting
confidence: 77%
“…Low IgG can be accompanied by low IgM and IgA in THI 21 . It was found that 26.4% of our patients had low IgA and 31.5% had low IgM along with low IgG in our patients.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Tregs can enhance MDSC function and control their differentiation through a mechanism involving TGF-β [ 27 ]. An earlier study of the relationship between MDSCs and Tregs in transient hypogammaglobulinemia suggested that its pathogenesis is based on the interplay between the MDSCs and Tregs [ 28 ]. However, until recently, the association of MDSCs and Tregs had not been examined in TDT.…”
Section: Discussionmentioning
confidence: 99%